Relationship between Attachment Style and Specialty Selection in Medical Interns in Ahvaz - Kianfar, Parisa; Sayahbargard, Mehdi; Rahim, Fakher (International Journal of Education and Cognitive Sciences, 2022)
Medical specialty selection is a critical issue that can have a direct impact on the health care workforce and affect the needs of the community health sector. Attachment styles, as one of the influencing factors in interpersonal interactions, can play a role in the specialty selection. The purpose of this study was to investigate the relationship between attachment styles and specialty selection in medical interns in Ahvaz. This is a descriptive epidemiological study. The study population consisted of medical interns from Jundishapur University of Medical Sciences in Ahvaz in 2018. The study selection method was convenience sampling. A questionnaire including the demographics, items regarding preferred and selected specialties, and Collins & Read Adult Attachment Scale were used for data collection. Data were analyzed using SPSS software. The most preferred specialties of the participants were cardiology (16%), general surgery (11.8%), and radiology (10.7%). The specialties mainly selected by the participants were radiology (21.9%) and dermatology (20.1%). 123 students (72.8%) had a secure attachment style, 36 (21.3%) had an anxiety attachment style, and 5 (3%) had an avoidant attachment style. The frequencies of preferred specialties were not significantly different in terms of attachment style (P = 0.339), the frequencies of the selected specialties were not significantly different in terms of attachment style as well (P = 0.774). The present study results showed no relationship between interns' attachment styles and their interest in their specialties.